(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Mishandling of biomedical waste has, and will continue to be, a serious threat to the health ofmedical professionals and the general population. The goal of this research was to identify and evaluatethe knowledge, attitudes, and behaviors of persons involved in biomedical waste management. A crosssectionalapproach was adopted for this investigation. Research was done at several medical facilities inRiyadh City, Saudi Arabia. Health workers in Riyadh City, Saudi Arabia, were the study’s population.There were 140 total healthcare professionals that took part in the research. Structured questionnairewas used to gather Quantitative data and analyzed using descriptive statistical methods guided by theStatistical Package for Social Sciences (SPSS) version 20. According to the results, almost all (96.5)healthcare personnel are aware that poor biomedical waste management might pose health risks. Nearlyall respondents (97.1) agreed that environmental issues were caused by improper handling ofbiological wastes. According to the survey, 73.2 percent of respondents said that cremation andthrowing biomedical waste into trash cans were the most common ways to dispose of such materials.The findings showed that most employees (80.3). had not gotten proper training on how to handlebiological waste. Saudi health care personnel in Riyadh City, Saudi Arabia, have a favorable attitude andperspective toward efficient management of health care waste, however they have poor practice when itcomes to biological waste. There is a pressing need in Saudi Arabia to establish a unified framework forthe collection, transportation, treatment, and disposal of biomedical wastes.